2023
DOI: 10.1186/s12904-022-01124-x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing palliative care capacity in primary care: study protocol of a cluster randomized controlled trial of the CAPACITI training program

Abstract: Background Primary care providers play a critical role in providing early palliative care to their patients. Despite the availability of clinical education on best practices in palliative care, primary care providers often lack practical guidance to help them operationalize this approach in practice. CAPACITI is a virtual training program aimed at providing practical tips, strategies, and action plans to provide an early palliative approach to care. The entire program consists of 12 sessions (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The ndings from this pilot study will be applied to the development of a national randomized controlled trial to compare the effectiveness of self-directed education alone versus education with facilitation, in the delivery of a three-part, revised version of CAPACITI. 44 A key limitation of this study is that not all teams participated in a focus group interview. Although we collected qualitative data from all teams, it is likely that those willing to participate in a focus group were more engaged in the CAPACITI program than those that did not, which may have biased our ndings.…”
Section: Discussionmentioning
confidence: 99%
“…The ndings from this pilot study will be applied to the development of a national randomized controlled trial to compare the effectiveness of self-directed education alone versus education with facilitation, in the delivery of a three-part, revised version of CAPACITI. 44 A key limitation of this study is that not all teams participated in a focus group interview. Although we collected qualitative data from all teams, it is likely that those willing to participate in a focus group were more engaged in the CAPACITI program than those that did not, which may have biased our ndings.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research found that patients may become disconnected from primary care upon entering the cancer system [ 32 , 33 , 34 , 35 ]; the patients in our study may have not yet re-engaged with their family physician. FDs have a key role in the initiation of EIPC, given the long-standing and integral care relationship they often have with their patients [ 36 , 37 ]. Moreover, collaborative care between FDs and oncology specialists has the potential to improve patient experience [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We implemented the modules leaving one-month in between to allow teams time to apply the teachings in practice. However, some found this time lengthy, making it difficult to maintain momentum, while others needed more time to complete the activities [ 62 ]. To shorten the length of CAPACITI while preserving the content and maintaining a stepwise implementation plan, we would divide the 10 session pilot program into three shorter modules that would each take 3 months to complete and could be taken solely or in succession.…”
Section: Discussionmentioning
confidence: 99%
“…There was an acceleration in the advent of self-directed online education with highly contextualized content as a result of the pandemic [ 63 65 A purely self-directed format may prove to be a cost-effective alternative to the live facilitated sessions we offered in CAPACITI and potentially preferred by participants as being more convenient. The findings from this pilot study will be applied to the development of a national randomized controlled trial to compare the effectiveness of self-directed education alone versus education with facilitation, in the delivery of a three-part, revised version of CAPACITI [ 62 ].…”
Section: Discussionmentioning
confidence: 99%